Negative media effects and Islamic remedies (penyelesaian kepada kesan negatif media menurut perspektif Islam) - Ishak, Mohd. Shuhaimi (International Islamic University Malaysia, 2010)
Generally speaking, media is extensively used as the means to disseminate news and information pertaining to business, social, political and religious concerns. A portion of the time and space of media has now become an important device to generate economic and social activities that include advertising, marketing, recreation and entertainment. The Government regards them as an essential form of relaying news and information to its citizens and at the same time utilizes them as a powerful public relations’ mechanism. The effects of media are many and diverse, which can either be short or long term depending on the news and information. The effects of media can be found on various fronts, ranging from the political, economic and social, to even religious spheres. Some of the negative effects arising from the media are cultural and social influences, crimes and violence, sexual obscenities and pornography as well as liberalistic and extreme ideologies. This paper sheds light on these issues and draws principles from Islam to overcome them. Islam as revealed to humanity contains the necessary guidelines to nurture and mould the personality of individuals and shape them into good servants.